Implementation of Electronic Governance Systems as a Tool for Establishing Effec-tive Society-State Communication - Melkonyan, Viktorya (YSU Journal of International Affairs, 2023)
In the modern world, electronic governance systems are tools for the easy access to information and its practical usage. The basis for their adoption is the vision of productive communication between state and citizen. The systems are aimed to strengthen democratic institutions and develop civil society by ensuring human rights and freedoms. Nevertheless, modern tendencies are accompanied with new challenges. In parallel with the process of digitalization, we encounter a set of problems related to information security such as issues of cybersecurity, non-reliable information, etc. From the other side, digitalization brings an antidemocratic discourse on the implementation of the right of citizens’ equal participation, the access and usage of all the necessary information and service portals, the functioning of sources which present public good and difficulties on proper feedback provision. This work discusses the importance of electronic governance systems in Armenia in establishing society-state constructive communication and the main achievements and challenges on the way of their adaptation. Nevertheless, modern tendencies accompanied with new challenges. In parallel with the process of digitalization, we encounter a set of problems related to information security such as issues of cybersecurity, non-reliable information, etc. From the other side, digitalization brings an antidemocratic discourse on the implementation of the right of citizens’ equal participation, the access and usage of all the necessary information and services portals, the functioning of sources which present public good and difficulties on proper feedback provision. This work discusses the importance of electronic governance systems in Armenia in establishing society-state constructive communication and the main achievements and challenges on the way of their adaptation.